Endotoxin-Induced Intravascular Clotting: the Need for Granulocytes - Lerner, R. G; Rapaport, S. I; Spitzer, Jane M. (Thrombosis and Haemostasis, 1968)
This study was undertaken to test the hypothesis that granulocytes are needed for intravascular clotting induced by endotoxin. Rabbits were treated with cortisone in a dosage that prepares for clotting after a single injection of endotoxin. They were divided into an experimental group, made granulocytopenic with nitrogen mustard before the injection of endotoxin, and 3 control groups. One control group was injected with saline; a second group was injected with endotoxin; a third group was made hypo coagulable with warfarin before the injection of endotoxin. The controls receiving endotoxin alone exhibited evidence of slow intravascular clotting lasting several hours: excess intravascular disappearance of 131I-fibrinogen and falls in fibrinogen levels, platelet counts, factor V and factor VIII activities. Factor VII and factor XII activities also fell in this group. Fibrin was seen in glomerular capillaries in many animals. The granulocytopenic animals experienced neither excess disappearance of intravascular fibrinogen nor fibrin deposition in the kidneys. Platelet counts fell slowly and clotting factor activities only slightly. Less evidence of intravascular clotting after endotoxin was found in the granulocytopenic animals than in the animals made hypocoagulable with warfarin. These data establish that granulocytes are required for endotoxin to induce significant intravascular clotting in animals prepared with cortisone.